Hyperprogressive Disease After Combined Anti-PD-L1 and Anti-CTLA-4 Immunotherapy for MSI-H/dMMR Gastric Cancer: A Case Report - Varnier, Romain; Garrivier, Thibaut; Hafliger, Emilie; Favre, Aymeric; Coutzac, Clélia; Spire, Clément; Rochefort, Pauline; Sarabi, Matthieu; Desseigne, Françoise; Guibert, Pierre; Cattey-Javouhey, Anne; Funk-Debleds, Pamela; et al. (Frontiers in Oncology, 2021)
Immune checkpoint inhibitors (ICI) have been developed in gastric adenocarcinomas and approved in first-line metastatic setting (in combination with chemotherapy) as well as in pretreated patients. Microsatellite instability-high (MSI-H) tumors are predicted to derive high benefit from ICI but data in gastric location are limited. Here, we described the case of a 68 years old patient with metastatic MSI-H gastric adenocarcinoma, referred to our center to receive immunotherapy after failure of standard of care (surgery with perioperative platin-based chemotherapy and paclitaxel plus ramucirumab at disease progression). The patient received one injection of durvalumab and tremelimumab and was hospitalized eighteen days after because of occlusive syndrome. The CT scan showed hyperprogression of the lymph nodes and hepatic lesions, compressing the gastric stump. He died few days after. Molecular analyses did not explain this outcome. To our knowledge, this is one of the firsts reported cases of hyperprogressive disease after combined ICI for a patient with MSI-H tumor. We reviewed the potential causes and discussed the emerging literature regarding predictive factors of hyperprogression in the particular subset of MSI-H patients. If some data were available in retrospective studies, validation of strong predictive factors is needed to avoid such dramatic evolutions.